Review of Nutrient Management Systems for Florida Vegetable Producers: A White Paper from the UF/IFAS Vegetable Fertilizer Task Force - Daniel Cantliffe; Phyllis Gilreath; Dorota Haman; Chad Hutchinson; Yuncong Li; Gene McAvoy; Kati Migliaccio; Teresa Olczyk; Steve Olson; Darrin Parmenter; Bielinski Santos; Sanjay Shukla; et al. (EDIS, 2009)
HS1156, a 14-page white paper from the UF/IFAS Vegetable Fertilizer Task Force, identifies differences between actual fertilization practices and UF/IFAS fertilizer recommendations, especially for vegetables grown with subsurface (Central and South Florida) and overhead (Miami-Dade County) irrigation. The recommendations of the VFTF aim at bridging the gaps between science-based results and the diversity in production systems found in the Florida vegetable industry. Includes references. Published by the UF Department of Horticultural Sciences, April 2009. Reviewed June 2012. This document previously published -- Proc. Fla. State Hort. Soc. 119:240-248.